INTEGRAÇÃO ENSINO SERVIÇO COMUNIDADE NA ATENÇÃO BÁSICA EM SAÚDE: UTOPIA OU REALIDADE? Dissertação - Bortoluz, Rafaela Ebre Guedes (2019)
The main objective of this study is to analyze the process of teaching service community integration in the scenarios of academic practices in Primary Health Care in Santa Maria RS, with the objective of reorienting vocational training to the Unified Health System. Its specific objectives are: to identify the perceptions of health students about the teaching service community integration in Health Units in which they perform practical activities and / or curricular in ternships; and to analyze aspects of the teaching service community integration process from the perspective of users assisted in Health Units that are configured as scenarios of professional health education. This is a mixed approach study, conducted in t hree Health Units, scenarios of health practice courses, located in a city in the central region of the state of Rio Grande do Sul. The eligible population consisted of 360 users and 207 students. Data collection was performed by a structured questionnaire composed of sociodemographic variables and questions related to the integration process, from March to August 2019. The analysis of quantitative data occurred with descriptive and inferential statistics. Qualitative data were subjected to content analysis Significant associations were considered when the results presented p <0.05. The study was approved by the University Ethics Committee, under number 2,449,070 and the ethical precepts of research with human beings were respected. Data analysis is present ed in the Results and Discussion chapter through two scientific articles, the first directed to the users' perception and the second to the students, regarding the teaching service community integration process. From the students' perspective, they view an d perceive as positive and promising the integration of the team in the learning process. They also identify strategies for improving this integration, such as multidisciplinary seminars, meetings and case discussions, improved communication, and the inclu sion of students in team action. With regard to users, most of them report recognizing the performance of the courses and evaluate them positively, however, there is still the challenge of strengthening the integration processes in order to make visible an d strengthen the performance of a larger number. health courses in practice settings. Still, users rated the quality of care received by students of nursing and medicine as excellent. The convergence of quantitative and qualitative findings was evidenced, regarding the positive aspects of the practice field, such as integration with the community, the reception and collaboration of professionals with students' learning. However, the perceptions of users and students about the integration process showed that this is a consolidating reality and that, for both populations, there is a predominance of a broader understanding of Primary Care, understanding it as a scenario of practice. effective for the student training process and integrated with the needs of the community. However, a relative distance between those involved in this process is visible. The insertion of students in the reality of services brings a formative perspective that fosters the articulation of the ideal and the real, opening possibilities f or new strategies for the implementation of the teaching service community integration process.